2012
DOI: 10.1165/rcmb.2011-0249oc
|View full text |Cite
|
Sign up to set email alerts
|

CD34+ Progenitor to Endothelial Cell Transition in Post-Pneumonectomy Angiogenesis

Abstract: In many species, pneumonectomy triggers compensatory lung growth that results in an increase not only in lung volume, but also in alveolar number. Whether the associated alveolar angiogenesis involves the contribution of blood-borne progenitor cells is unknown. To identify and characterize blood-borne progenitor cells contributing to lung growth after pneumonectomy in mice, we studied wild-type and wild-type/green fluorescence protein (GFP) parabiotic mice after left pneumonectomy. Within 21 days of pneumonect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 48 publications
2
36
1
Order By: Relevance
“…The mechanism responsible for this structural damping is unclear, but likely reflects components intimately involved in tissue regeneration including proliferating cells, extracellular connective tissue and the alveolar air-liquid interface [28, 29]. Consistent with this interpretation, our data demonstrated a significant change in tissue damping coincident with the maximal growth phase; that is, the phase of lung growth associated with cellular proliferation and gene transcription [12-14]. We speculate that the return to baseline G and H was a reflection of neoalveolarization.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The mechanism responsible for this structural damping is unclear, but likely reflects components intimately involved in tissue regeneration including proliferating cells, extracellular connective tissue and the alveolar air-liquid interface [28, 29]. Consistent with this interpretation, our data demonstrated a significant change in tissue damping coincident with the maximal growth phase; that is, the phase of lung growth associated with cellular proliferation and gene transcription [12-14]. We speculate that the return to baseline G and H was a reflection of neoalveolarization.…”
Section: Discussionsupporting
confidence: 75%
“…Recent studies of post-pneumonectomy lung cells [12], including endothelial cells [13, 14] and alveolar macrophages [15], have demonstrated an unexpected transcriptional time course; that is, gene transcription and cell proliferation that are minimal at 3 days, but peak 6 to 7 days after pneumonectomy. Distinct from the stretch responses studied in vitro—typically detected within hours of the stretch signal—these results indicate that post-pneumonectomy mechanics may not be optimally characterized as an immediate one-time stretch signal, but rather as dynamic anatomical and mechanical adaptations to the post-pneumonectomy thorax that occur over days to weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, parabiosis provides a fate map of cell migration without bone marrow transplantation or ex vivo labeling. Using the parabiosis model we have demonstrated dramatic numbers of EPCs migrating to, and integrating into, the vascular endothelium of the growing mouse lung (66). …”
Section: Pillar Extensionmentioning
confidence: 99%
“…First, studies in both humans and rodents have demonstrated the importance of macrophages in maintaining the hematopoietic stem cell niche (Ehninger and Trumpp, 2011). The recent finding that blood-borne CD34 + progenitor cells contribute to compensatory lung growth (Chamoto et al, 2011) suggests that alveolar macrophages may participate in regulating alveolar construction. Second, tissue macrophages have been shown to regulate epithelial proliferation (Cakarova et al, 2009) as well as neovascularization and vascular stabilization (Sunderkotter et al, 1994) Both epithelial proliferation and alveolar angiogenesis are central features of post-pneumonectomy lung growth.…”
Section: Introductionmentioning
confidence: 99%